Glosa do uchwały składu 7 sędziów Sądu Najwyższego z dnia 25 stycznia 2018 r., I KZP 12/17 - Czerwińska, Dorota (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
In the commented judgment the Supreme Court took the view that the interlocutory appeal against the appellate court’s refusal to accept the party’s motion for the statement of reason of a judgment is inadmissible in proceedings concerning misdemeanours. According to the Supreme Court, such conclusion may be derived from the principle of non-appeal from the decisions of appellate courts. It is also supported by the fact that the judgment of the appellate court in such proceedings is not subject to cassation, so the written statement of reason is only for information purposes. The author of this commentary disagrees with the thesis and its justification. In the paper, the views of doctrine and judicature are analysed, viewing statement of reasons as part of the fair trial and procedural fairness standard, which should be guaranteed regardless of whether the judgment is still subject to appeal or cassation. The statement of reason is of such importance to the parties and society that there is no basis for differentiating the standard in criminal proceedings and in proceedings concerning misdemeanors in this respect.
Keywords: statement of reason; motion to prepare a statement of reason in writing; fair trial; procedural fairness; interlocutory appeal; proceedings concerning misdemeanors